Second sight : the visionary imagination in late Victorian literature - Maxwell, Catherine, 1962- (Manchester University Press ; Distributed in the USA exclusively by Palgrave Macmillan, 2009)
An innovative reassessment of late Victorian literature in its relation to visionary Romanticism. It examines the subject in relation to a range of writers of the period, including Pater Rossetti, Hardy and Vernon Lee.
Keywords: English literature -- 19th century -- History and criticism.; Romanticism.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Romantisme.; romanticism (form of expression); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English literature; Romanticism; 1800-1899; Criticism, interpretation, etc.